Evaluasi Program Rumah Tidak Layak Huni (RTLH) di Kota Solok - Ilda, Adelia Kurniati; Yuliarti, Yuliarti (Lembaga Yasin AlSys, 2025)
The high number of uninhabitable houses (Rumah Tidak Layak Huni, RTLH) in Solok City, despite the implementation of the RTLH improvement program since 2017. The research aims to evaluate the implementation of the RTLH Program by the Solok City Housing and Settlement Area Office and to identify the inhibiting factors affecting its execution. A qualitative approach with a descriptive method was used, with data collected through interviews, documentation, and observation. Data validation was carried out using triangulation techniques. The findings show that the RTLH program has had a positive impact on improving the quality of housing and the well-being of its beneficiaries. However, the implementation still faces several obstacles, including low levels of community self-help participation, delays in the distribution of building materials, and administrative barriers, particularly regarding proof of land ownership. The study concludes that although the RTLH program is relatively effective and efficient, improvements in supervision, data management systems, and more targeted outreach strategies are necessary to maximize the program’s long-term benefits for low-income communities.